HUBUNGAN TEKNIK DISTRAKSI DENGAN TINGKAT NYERI AKIBAT PEMASANGAN INFUS PADA ANAK USIA 3-5 TAHUN DI RS SULTAN SULAIMAN - Munir, Chairul; Rizky Safitri Matondang, Elsa; Rahman Aceh, Arif (Jurnal Ilmu Keperawatan, 2023)
Infusion is an invasive procedure performed by inserting an intravenous catheter for the purpose of treatment or rehydration. The purpose of this study was to determine the relationship between distraction techniques and the level of pain due to infusion in children aged 3-5 years who were treated at Sultan Sulaiman Hospital with the correlation method using a cross-sectional design. The population in this study were pre-school age children (3-5 years) who were treated in the children's room at the Sultan Sulaiman Hospital with an average visit of 59 people/month and a sample of 38 children was taken using purposive sampling technique. The data were analyzed by using Chi-Square Correlation analysis test. The results of the study most of the respondents with pain scale 3 were 21 respondents (55.3%). and most of the respondents who gave distraction techniques according to SPO were 25 nurses (65.8%). Based on the analysis test of the relationship between pain levels due to infusion with distraction techniques in children aged 3-5 years at Sultan Sulaiman Hospital, this is marked by a P value = 0.000. For further research, it is expected to use more complete methods such as observation and interviews.